Analisis Pasca Merger: Komparasi Tingkat Kesehatan Bank Syariah Dengan Bank Konvensional di Indonesia - Ilham Wanakusuma; Dwi Retno Widiyanti (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study is to show a comparison of the soundness level of Islamic bank with conventional banks, namely Bank Syariah Indonesia (BSI), Bank Tabungan Pensiunan Nasional (BTPN), and Bank Danamon with a period of two years after the merger through the RGEC approach as measured by the financial ratio NPF/ NPL, FDR/LDR, ROA, and CAR. Quantitative methods are used to retrieve secondary data on financial ratios sourced from financial reports on the official website of OJK and related banks. Hypothesis testing was carried out using the One Way ANOVA and Kruskal-Wallis Test. This study succeeded in showing that there is a significant difference in the soundness of banks two years after the merger in terms of the overall ratio. BSI excels in the FDR/LDR ratio, Danamon excels in the ROA and CAR ratios, and BTPN excels in the NPF/NPL ratio. BSI and Danamon showed healthy overall financial ratios and were considered capable of carrying out their intermediary function properly, while BTPN was considered less than optimal, due to one of the ratios, namely unhealthy liquidity. Mergers do not always have a positive impact on the soundness level of banks therefore it is hoped that the banks that are going to merge can take preventive steps and develop appropriate policies in order to maintain their soundness level.